Optimization of the demineralization process of black soldier fly (Hemertia illucens) pupa shell maggot chitosan and the physicochemical characteristics - Mira Maulidina; Muhammad Rifqi; Siswanto (Menara Perkebunan, 2024)
Chitosan is a derivative compound of chitin that has undergone deacetylation. Chitosan has three stages of the manufacturing process, including demineralization, deproteinization, and deacetylation. Chitin is also found in the black soldier fly maggot pupae, but maggot pupae contain high minerals content that can affect the purity of the resulting chitosan. Therefore, demineralization treatment is necessary to remove minerals from maggot pupae shells. This study aims to optimize the demineralization process by finding the best type of acid solvent, the best incubation time, and combination treatments. The black soldier fly (BSF) maggot pupa shell was soaked using various formic acid, hydrochloric acid, and nitric acid solutions with incubation times of 60, 120, and    180 minutes. Chitosan characterization was carried out following SNI 7949:2022, including water content, ash content, nitrogen content, pH, deacetylation degree, characterization of functional groups with FT-IR, and as an antimicrobial comparison is formalin. The best demineralization treatment was obtained at 0.5 M nitric acid treatment with an incubation time of   120 minutes. The characterization of chitosan produced 7.81% water content, 0.56% ash content, 4.73% nitrogen content, pH 7.39, and 75.14% deacetylation degree. Characterization of groups on chitosan with FT-IR resulted in the absorption of O-H and N-H groups 3484 cm-1 and 3152 cm-1; C-H 2877 cm-1; and C=O 1653 cm-1. The inhibitory power against E. coli of the BSF maggot pupa shells chitosan is better compared to chitosan standard but not better than formalin.